2021
DOI: 10.4103/jfmpc.jfmpc_1524_20
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and contributing factors for adolescent obesity in present era

Abstract: Background: Adolescent obesity is a very common issue in our culture. Recent studies have shown that this is a form of global burden that may predispose factors in advanced life for many other diseases. Adolescents are a positive force for a country, responsible for their future prosperity and also for their nations. Objectives: The main objective of the study was to identify the prevalence of obesity among adolescents and its diverse contributing factors. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
17
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 17 publications
3
17
1
1
Order By: Relevance
“…11 Many studies in India have reported that hypertension caused cardiovascular diseases beginning in the age group of children and adolescents. 8 A study results showed that prevalence of hypertension was 11% among school children in the age group of 13 to 19 years in the five schools of Udaipur city of Rajasthan. 8,9 In India, approximately 18.3% of female adolescents aged between 2 and 17 years are either in the category of overweight or obese.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Many studies in India have reported that hypertension caused cardiovascular diseases beginning in the age group of children and adolescents. 8 A study results showed that prevalence of hypertension was 11% among school children in the age group of 13 to 19 years in the five schools of Udaipur city of Rajasthan. 8,9 In India, approximately 18.3% of female adolescents aged between 2 and 17 years are either in the category of overweight or obese.…”
Section: Introductionmentioning
confidence: 99%
“…7 Global status report on NCDs-2014 by the World Health Organization (WHO) shows that NCDs are responsible for approximately 1.2 million deaths worldwide each year in the age group below 20 years, and around 60% of deaths happen in India due to NCDs. 8 Globally, the magnitude of overweight and obesity and its impact have increased. 2 An unhealthy lifestyle can contribute to the development of risk factors for NCDs.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, are a good force for a country, accountable for their future success as well as the prosperity of their nations. Nearly 35% of the global burden of disease has its root emergence in adolescence (Prasad, Bazroy, & Singh, 2016), (Seema et al, 2021). Adolescent obesity is among the twenty-first century's most significant public health issues.…”
Section: Introductionmentioning
confidence: 99%
“…Obesity has been a global public health concern which has caused various health problems and social burden [ 5 , 6 ]. Recent work has indicated that obesity has become widespread in adolescents as well as in young and older adults [ 7 , 8 ], with an increasing trend in recent decades [ 9 ].…”
Section: Introductionmentioning
confidence: 99%